PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SDN 014 SILIKUAN HULU KECAMATAN UKUI KABUPATEN PELALAWAN - Ritmiyati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes in Science (IPA) for grade II SDN 014 Silikuan Hulu. Of the 27 students, only 12 students or 44.5% completed the results of their study, while the average value of student learning outcomes is 64.4. This learning outcome is still low by the KKM (Minimum Completeness Criteria) set at 70. Based on this, the researchers conducted a classroom action research by implementing the STAD (Student Teams Achievement Divisions) cooperative learning model with the aim to improve learning outcomes in Science. This study was conducted over two cycles, each cycle consisting of two meetings and one daily test. The instruments used were observation sheet activities of teachers and students and science achievement test. The data collection technique used is the technique of observation and testing techniques. The results showed that after the implementation of the STAD cooperative learning model, teacher and student activity increased. In the first cycle, the first meeting of teachers was categorized as moderate activity, with a total score of 16 or 66.7%. At the second meeting, it increased with a total score of 18 or 75% in the